2019
DOI: 10.1007/s11896-019-09324-7
|View full text |Cite
|
Sign up to set email alerts
|

Enjoying Police Duties: Public Service Motivation and Job Satisfaction

Abstract: Public service motivation briefly described as the motivation to contribute to society well-being is a continuously growing topic in the field of public administration. This concept, however, has not been widely applied to the distinct work environment of police forces. Addressing the gap, two studies look at the relationship between public service motivation and job satisfaction and the way this relationship is mediated by person-job and person-organization fits. The data comes from Warsaw (Poland) city polic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 72 publications
(94 reference statements)
3
13
0
Order By: Relevance
“…The result is consistent with Vorina et al, (2017) who found that engagement has significantly influenced job satisfaction. The result agrees with the results from Prysmakova & Vandenabeele (2019) who reported that employees with higher levels of motivation have higher levels of job satisfaction.…”
Section: Results Of Hypothesis Testingsupporting
confidence: 92%
See 1 more Smart Citation
“…The result is consistent with Vorina et al, (2017) who found that engagement has significantly influenced job satisfaction. The result agrees with the results from Prysmakova & Vandenabeele (2019) who reported that employees with higher levels of motivation have higher levels of job satisfaction.…”
Section: Results Of Hypothesis Testingsupporting
confidence: 92%
“…The research was conducted among employees of telecommunication companies in Pakistan. Prysmakova & Vandenabeele (2019) confirmed that employees with higher level of motivation have higher levels of job satisfaction. The data was obtained from Polish and Belgian police officers.…”
Section: Employee Motivationmentioning
confidence: 66%
“…Similar to POP theory, PO fit theory suggests that employees will have more beneficial work attitudes and behaviors when there is congruence between their personal characteristics and those of their organization (Kristof, 1996). Interestingly, in the field of public management, there is also evidence that PSM is positively related to PO fit and that PO fit fully mediates the effects of PSM on self-reported performance (Bright, 2007; Van Loon et al, 2017), job satisfaction (Bright, 2008; Prysmakova & Vandenabeele, 2020; Teo et al, 2016), and turnover intentions (Bright, 2008; Gould-Williams et al, 2015). In many ways, POP can be considered to be another dimension of congruence that reflects the alignment between public employees’ own beliefs and their understanding of citizens’ beliefs about their employment organizations.…”
Section: Psmmentioning
confidence: 99%
“…Research with nurses in Italy has demonstrated that PSM has a positive relationship with job satisfaction and performance and that this relationship is amplified in the presence of transformative leadership strategies that highlight for the nurse the prosocial impact they have had on those they serve (Belle, 2013). Research with police has demonstrated that PSM is positively correlated with job satisfaction, particularly when there is a good fit between the person with the job tasks and with organizational culture (Prysmakova & Vandenabeele, 2019). Qualitative research with police officers in Switzerland (Neumann et al, 2019) has found that PSM and prosocial motivation are distinct among police officers and can vary independently.…”
Section: Literature Reviewmentioning
confidence: 99%